Who Consumes the Credit Union Subsidies? - Robert DeYoung; John Goddard; Donal G. McKillop; John O. S. Wilson (Queen's University Belfast, Queen's Management School, 2022)
We estimate a structural profit model for 956 matched pairs of US credit unions and commercial banks, using the results to examine how the subsidies associated with credit unions' income tax exemptions and non-profit status are allocated across various stakeholders. We find economically large profit inefficiencies at credit unions relative to banks—a little more than half of which is supported by their tax subsidy, but over 90 percent of which is passed through to credit union members as above-market deposit interest rates. Given extensive evidence collected elsewhere that credit union members tend to earn above-average incomes, our results indicate a serious misalignment between the legislation that establishes the credit union mission (a tax exemption in exchange for meeting the credit and savings needs of consumers, especially those of modest means) and the actual performance of credit unions under that legislation.
Keywords: G21; G28; 330; Commercial banks; credit unions; profit inefficiency; tax exempt status